Chemical, electrochemical, quantum, and surface analysis evaluation on the inhibition performance of novel imidazo[4, 5-b] pyridine derivatives against mild steel corrosion. (15th August 2021) - Saady, A.; Rais, Z.; Benhiba, F.; Salim, R.; Ismaily Alaoui, K.; Arrousse, N.; Elhajjaji, F.; Taleb, M.; Jarmoni, K.; Kandri Rodi, Y.; Warad, I.; Zarrouk, A.
Graphical abstract: Highlights: New imidazo[4, 5-b] pyridine derivatives were used are effective corrosion inhibitor for mild steel. Anti-corrosion activity was performed using weight loss and electrochemical techniques. Surface analysis has been performed by UV–vis and SEM/EDX. Experimental results have been combined by theoretical studies (DFT and MD). Abstract: In this article, we evaluated the inhibitory performance of imidazo[4, 5-b] pyridine derivatives namely, 6-bromo-2-(4-chlorophenyl)-3-(prop-2-yn-1-yl)-3H-imidazo[4, 5-b]pyridine(SB9a) and 6-bromo-2-(4-chlorophenyl)-3-decyl-3H-imidazo[4, 5-b]pyridine (SB14a) against mild steel (MS) corrosion in 1 M HCl using weight Loss from 303 to 333 K, Potentiodynamic Polarization (PDP), Electrochemical Impedance Spectroscopy (EIS), Scanning Electron Microscopy (SEM), energy dispersive X-ray (EDX) analysis, UV–vis spectroscopy and computational approach. The studied inhibitors showed a high inhibition performance since achieving a percentage of 90 % for SB14a and 88 % for SB9a 0.1 mM. PDP indicates that the both derivatives behaved as mixed-type inhibitors. Density functional theory (DFT) and molecular dynamic simulation (MD)) supports the experimental results.